ANALYSIS OF IMPROVING PERSONAL EXPERIENCE WRITING SKILLS USING CONTEXTUAL METHODS AT CLASS VII STUDENTS OF SMP IT WIHDATUL UMMAH KOLAKA - J. Jumriah; T. Takwa (Universitas Sembilanbelas November Kolaka, 2018)
Writing skill is a process of thinking or pouring ideas outlined in writing. Through this thought process, students find it difficult to put their ideas into writing so that writing activities are still very low. Specifically, this study aims: (1) to describe the learning outcomes of the analysis of increasing personal experience writing skills in class VII students of Wihdatul Ummah Middle School before learning to write personal experiences with contextual methods, (2) to describe the learning outcomes of personal experience writing skills improvement analysis in the seventh grade students of Wihdatul Ummah Middle School after a personal experience writing learning with contextual methods, (3) to describe the learning outcomes of analysis of personal experience writing skills improvement for VII grade students of Wihdatul Ummah Middle School before and after learning to write personal experiences with contextual methods. This research was carried out in Kolaka district, precisely in SMP IT Wihdatul Ummah Kolaka. This study uses a class action research design (CAR). This research was carried out through several processes (cycle I and cycle II), namely: (1) planning, (2) action, (3) observation or observation, (4) reflection. If the first cycle of action on the average value of students has not reached the predetermined target, then the second cycle will be carried out. Data collection techniques in this study are test techniques and non-test techniques. The data analysis technique used is descriptive qualitative analysis that gives an idea of whether or not there is an increase in personal experience writing skills using contextual methods. Based on the results of the study, the increase in the ability to write personal experiences using contextual methods increased from the average value in the pre-cycle 64.23 or the less category, increasing in cycle 1 with an average value in the first cycle of 65 but still lacking category, while the increase seen in the second cycle with an average score of 82 or categorized very well and achieved a minimum completeness criterion (KKM) of 70 and reached the target set by the researcher which was 75% or very good.